1995
DOI: 10.1021/jm00005a006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti-HIV-1 Activity of 4,5,6,7-Tetrahydro-5-methylimidazo[4,5,1-jk][1,4]benzodiazepin-2(1H)-one (TlBO) Derivatives. 4

Abstract: In previous papers, we have described the discovery of a new series of compounds, 4,5,6,7-tetrahydro-5-methylimidazo[4,5,1-jk][1,4]benzodiazepin-2(1 H)- ones, TlBO (1 and 1a), with potent anti-HIV-1 activity and the synthesis of analogues to better define the structure-activity relationships (SAR) in terms of changes in substituents at the N-6 position and variations of the five-membered urea ring as well as the seven-membered diazepine ring. This paper describes the synthesis of TlBO analogues with various su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 8 publications
1
42
0
Order By: Relevance
“…The drugs used in this study were: carboxanilides UC781, UC10, UC38, UC84 (24,25), Uniroyal Chemical (Middlebury, CT); EFV (21), DuPont Merck; BHAP (26), Amersham Pharmacia and Upjohn; nevirapine (19), Roxanne Laboratories (Redding, CT); (S)-4-isopropoxycarbonyl-6-methoxy-3-(methylthiomethyl)-3,4-dihydroquinoxaline-2(1H)-thione (HBY 097) (27), Hoechst-Bayer (Frankfurt, Germany); and (Ϫ)-(S)-8-chloro-4,5,6,7-tetrahydro-5-methyl-6-(3-methyl-2-butenyl)imidazo [4,5,1-jk] [1,4]benzodiazepin-2(1H)-thione monohydrochloride (8 Cl-TIBO) (28) and ␣-anilinophenylacetamide (␣-APA) (29), Janssen. All drugs were dissolved in dimethyl sulfoxide at a concentration of 10 mg͞ml for use in Y2H and in vitro assays.…”
Section: Methodsmentioning
confidence: 99%
“…The drugs used in this study were: carboxanilides UC781, UC10, UC38, UC84 (24,25), Uniroyal Chemical (Middlebury, CT); EFV (21), DuPont Merck; BHAP (26), Amersham Pharmacia and Upjohn; nevirapine (19), Roxanne Laboratories (Redding, CT); (S)-4-isopropoxycarbonyl-6-methoxy-3-(methylthiomethyl)-3,4-dihydroquinoxaline-2(1H)-thione (HBY 097) (27), Hoechst-Bayer (Frankfurt, Germany); and (Ϫ)-(S)-8-chloro-4,5,6,7-tetrahydro-5-methyl-6-(3-methyl-2-butenyl)imidazo [4,5,1-jk] [1,4]benzodiazepin-2(1H)-thione monohydrochloride (8 Cl-TIBO) (28) and ␣-anilinophenylacetamide (␣-APA) (29), Janssen. All drugs were dissolved in dimethyl sulfoxide at a concentration of 10 mg͞ml for use in Y2H and in vitro assays.…”
Section: Methodsmentioning
confidence: 99%
“…2) with S configuration was found to be active, showing that this configuration is required for the anti-HIV-1 properties of TIBOs (Pauwels et al, 1990). The subsequent studies aimed at the evaluation of systematic alterations in the structure of the lead compound, and its scaffold was independently modified in four different portions: the substituent bonded to the 6-positon nitrogen of the diazepine ring (Kukla et al, 1991a), the 5-ring urea portion (Kukla et., 1991b), the 7-membered ring portion and the substituent of the aromatic ring (Ho et al, 1995). The results obtained in these studies are described in the next sections.…”
Section: Sar Of Tibo Derivativesmentioning
confidence: 95%
“…Furthermore, the substitutions at 9-positon led to the formation of compounds, whose activities are similar to those of the parent unsubstituted compound, while 10-substituted compounds were found to be less active. The replacement of the aromatic ring by a heteroaromatic ring was also evaluated, but the derivatives were inactive (Ho et al, 1995).…”
Section: Evaluation Of Substituent Effect On the Aromatic Ringmentioning
confidence: 99%
“…Two sets of data have been employed for the present analysis: TIBO derivatives and HEPT derivatives ( Figure 1). In a series of studies Ho et al demonstrated that certain compounds of type 1 show anti-HIV-1 activity by functioning as non-nucleoside reverse transcriptase (RT) inhibitors [44]. They systematically synthesized and tested numerous members of this family, differing in substituents X, Y, Z, and R. Here, Z was restricted to oxygen and/or sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…The X can be oxygen or sulfur however, it was observed that the former tends to produce a higher level of activity. Effectiveness in inhibiting HIV-1 was measured by the concentration of the compound, C 50 , required to achieve 50 % protection of MT-4 cells against the virus [6,44,45]. We considered the experimental results for thirty eight TIBO and nineteen HEPT derivatives as representative for developing regression equations for anti-HIV-1 potencies of these classes of compounds.…”
Section: Introductionmentioning
confidence: 99%